y = ax² + bx + c - postać ogólna funkcji kwadratowej
y = a(x - p)² + q - postać kanoniczna funkcji kwadratowej
1.
y = (x - 3)² - 2 = x² - 6x + 9 - 2
y = x² - 6x + 7 - postać ogólna
2.
y = -2x² + 3x - 6
a = -2, b = 3, c = -6
y = a(x - p)² + q
[tex]p = \frac{-b}{2a} = \frac{-3}{2\cdot(-2)} = \frac{-3}{-4} = \frac{3}{4}\\\\q = \frac{-\Delta}{2a} = \frac{-[3^{2}-4\cdot(-2)\cdot(-6)]}{2\cdot(-2)}=\frac{-(9-48)}{-8} = \frac{-(-39)}{-8} =- \frac{39}{8}=-4\frac{7}{8}\\\\y = -2(x - \frac{3}{4})^{2}-4\frac{7}{8} \ - \ postac \ kanoniczna[/tex]
3.
A.
x² - 3x = 0
x(x - 3) = 0
x = 0 ∨ x - 3 = 0
x = 0 ∨ x = 3
x ∈ {0; 3)
B.
x² - 9 = 0
(x + 3)(x - 3) = 0
x + 3 = 0 ∨ x - 3 = 0
x = -3 ∨ x = 3
x ∈ {-3;3}